OBSERVATION ON THE URINOGENITAL PAPILLA AND SEXUAL DIMORPHISM IN SOME INDIAN GOBIIDS (GOBIIDAE: TELEOSTEI) - HAR, SAKTI P (Journal of Indian Fisheries Association, 2015)
A thorough comparative study on the urinogenital papilla and sexualdimorphism has been made for the first time in both the sexes of twelve Indiangobiids- Glassogobius giuris (Han1ilton); Acentrogobius cyanomos (Bleeker);Eleotriodes muralis (Valenciennes); Parapocryptes serperaster (Richardson);Apocryptes bato (Hamilton); Scartclaos viridis (Hamilton); Boleophthalmusboddarti (Pallas), Periophthalmus schlosseri (Pallas); P. koelreuteri (Pallas);Taenioides anguillaris (Linnaeus); T. buchanani (Day); Odontamblyopusrubicundus (Hamilton). The urinogenital papilla, originating as a free muscularorgan from the ventral surface of the body-wall and shortly behind anus, ispresent in both the sexes. It is an important organ of primary sex recognitionin all species. In case of male the papilla is conical, broad at the base andin female it is either flattened, distally truncated or bluntly rounded. Thepresence of permanent colour mark over the specific region of the bodysurface is another secondary sexual character in a few species. Besides,colouration may also be a nuptial secondary sex character developed in someduring peak breeding season. The enlargement and colouration of the organ issubject to seasonal variations parallel to the seasonal gonadal cycle. Thehistological architecture of the papilla shows a high degree of cellularspecialization and an interrelationship to the urinary and genital ducts. Thefunctional efficacy and significance of the papilla in the breeding biology ofthese fishes has been discussed.Keywords : Gobiidae, Sexual dimorphism, Urinogenital papilla